Open The Philosophy and Practices that are Revolutionizing Education and Science - Biswas-Diener, Robert; Jhangiani, Rajiv (Ubiquity Press, 2017)
"Affordable education. Transparent science. Accessible scholarship. These ideals are slowly becoming a reality thanks to the open education, open science, and open access movements. Running separate-if parallel-courses, they all share a philosophy of equity, progress, and justice. This book shares the stories, motives, insights, and practical tips from global leaders in the open movement."